Plant protein-based feeds and commercial feed enable isotopic tracking of aquaculture emissions into marine macrozoobenthic bioindicator species. Issue 3 (4th May 2017) - Kusche, Henrik; Hillgruber, Nicola; Rößner, Yvonne; Focken, Ulfert
ABSTRACT: Brittle stars ( Ophiura spp.) and other benthic macrofauna were collected in a prospective mariculture area in the North Sea to determine if these taxa could be used as indicator species to track nutrients released from future offshore aquaculture sites. We analysed natural carbon and nitrogen stable isotopic signatures in tissues from macrofauna and compared these to six feed ingredients and four experimental diets made thereof, as well as to a commercial feed with and without lipid and carbonate removal. Our data suggest practicability of using isotopic signatures of Ophiura spp. to track aquaculture-derived organic material if plant-based fish diet ingredients and commercial feed were used for fish farming in the German Exclusive Economic Zone. Diets with high fish meal content would not be detected in Ophiura spp. using isotopic measures due to the similarity with the marine background. Our data provide valuable baseline information for studies on the impact of offshore aquaculture on the marine environment.